Personality Traits and Physical Activity: Helping Exercise Professionals Maximize Client Outcomes. (July 2021) - Newsome, A'Naja; Kilpatrick, Marcus; Mastrofini, Gianna; Wilson, Kathryn
Abstract : Personality traits are useful for exercise professionals in understanding individual differences in exercise preferences and behaviors and can lead to better rapport and ultimately maximize performance. Apply It: Understand the relationship between personality traits and exercise behaviors Integrate personality scales as meaningful tools for client goal setting and exercise programming Identify strategies for using personality traits to increase client performance